Glycemic Variability and Prognosis of Patients with Intracerebral Hemorrhage: A Meta-Analysis - Jiao, Xu; Wang, Huifang; Li, Mingfei; Lu, Yun (Hormone and Metabolic Research, 2023)
Glycemic disorder may affect the outcomes of patients with intracerebral hemorrhage (ICH). However, the association between glycemic variability (GV) and prognosis in these patients remains to be determined. We performed a meta-analysis to compressive the influence of GV on functional outcome and mortality in patients with ICH. Observational studies comparing the risks of poor functional outcome (defined as modified Rankin Scale>2) and all-cause mortality between ICH patients with higher versus lower acute GV were retrieved by systematic search of Medline, Web of Science, Embase, CNKI, and Wanfang databases. A random-effect model was used to pool the data after incorporating the between-study heterogeneity. Sensitivity analyses were performed to evaluate the stability of the findings. Eight cohort studies involving 3400 patients with ICH were included in the meta-analysis. The follow-up duration was within 3 months after admission. All of the included studies used standard deviation of blood glucose (SDBG) as the indicator of acute GV. Pooled results showed that ICH patients with higher SDBG were associated with a higher risk of poor functional outcome as compared to those with lower SDBG [risk ratio (RR): 1.84, 95% confidence interval (CI): 1.41 to 2.42, p<0.001, I2=0%]. In addition, patients with higher category of SDBG were also associated with a higher mortality risk (RR: 2.39, 95% CI: 1.79 to 3.19, p<0.001, I2=0%). In conclusion, high acute GV may be a predictor of poor functional outcome and mortality of patients with ICH.
Keywords: intracerebral hemorrhage; glycemic variability; mortality; functional outcome; meta-analysis